Postradiative stenosis of the spinal canal: features of the clinic, diagnosis and treatment (clinical case) - O. V. Sklyarenko; S. N. Larionov; A. P. Zhivotenko; V. A. Sorokovikov; A. V. Gorbunov; V. E. Potapov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Postradiation epidural fibrosis is one of the rare complications of cancer treatment in patients receiving radiation therapy, leads to a mosaic clinical picture, including manifestations of polyneuropathy, caudogenic intermittent lameness syndrome and can significantly affect the quality of life of patients. Depending on the type of cancer, the volume of the affected tissues and the level of damage to the spine, radiation fibrosis syndrome is characterized by a diverse clinical picture. The main clinical manifestations of post-radiation fibrosis of the spinal canal at the level of the lumbar spine are pain, numbness, paresthesia in the lower extremities. A thorough history and physical examination, combined with the use of neuroimaging data, help establish an accurate diagnosis and select an effective treatment. When studying the problem of post-radiation fibrosis, it is extremely difficult to predict the time, risk group and specificity of characteristic symptoms, given the development of pathology in elderly and senile patients, against the background of existing degenerative changes in the spine. However, there is a close relationship with dosage, anatomical impact, nature of damage and clinical symptoms. Conservative methods of treating post-radiation fibrosis with spinal canal stenosis include the use of analgesic, antiinflammatory therapy. With a prolonged course of pain syndrome, insufficient effectiveness of conservative treatment, local blockades or epidural injections are carried out. In the absence of the effect of conservative treatment, indications for surgical intervention arise.